3-phase 4-wire shunt active power filter with renewable energy interface - Pinto, J. G. (2007)
This paper presents a three-phase four-wire Shunt Active Filter that compensates power quality problems and can also interface renewable energy sources with the electric grid. The inverter stage of the active filter is based in a two level four leg inverter and its control is based in the Theory of Instantaneous Reactive Power (p q Theory). The filter is capable of compensating power factor, unbalance, and current harmonics. Additionally it can also make the interface between renewable energy sources and the electrical system, injecting balanced practically sinusoidal currents (with low THD).